The Influence of Social Media on Problem Solving Abilities Through Digital Literacy in Adolescents - Ferawati, Annisa Udtafia; Setyowati, Dewi Liesnoor; Husain, Fadly (Universitas Negeri Semarang, 2025)
In the digital era, social media has become an integral part of teenagers' lives, playing a significant role in shaping their behavior and cognitive abilities, particularly problem-solving skills. Research indicates that social media can have both positive and negative impacts on these abilities, depending on the quality of interactions and digital literacy. Further research is needed to deeply understand how social media use affects problem-solving skills and the role of digital literacy as a mediating variable that strengthens the relationship between social media use and problem-solving abilities in teenagers. This study employed a quantitative method using path analysis. The subjects were teenagers aged 15-18 living in Semarang City, with a sample of 369 students. The results show that social media significantly influences teenagers' digital literacy by 40%, but does not directly affect problem-solving skills. Instead, social media affects problem solving indirectly through digital literacy, with a total effect of 19.2%. Digital literacy itself has a significant impact of 23.1%, aiding teenagers in problem solving through skills in searching, evaluating, and managing digital information. These findings underscore the need to focus on digital literacy to optimize the positive impact of social media on teenagers' problem-solving skills.